Relações interpessoais nas organizações: a inteligência espiritual como potencial para auxiliar os líderes nesse processo - Santos, Sheila Seberino Sampaio dos (Universidade do Vale do Rio dos Sinos, 2019)
This research sought to understand how Spiritual Intelligence can enhance the development of leaders, through a conceptual plan, to improve relationships in work environments in the area of IT and digital business. This journey involves the analysis of the work environment, identifying the main elements of satisfaction and dissatisfaction and their impacts on the work, and the main elements that influence the interpersonal relations. A qualitative exploratory study was carried out, where the data were collected through face-to-face interviews with 23 employees from five medium-sized IT companies and digital businesses located in the city of Porto Alegre / RS, Brazil. The data collected in the interviews using a semi-structured script were analyzed through the technique of content analysis (BARDIN, 2010), following three steps: 1) pre-analysis of the material; 2) exploration of the material in which the categories were defined a posteriori, emerging from the speech and content of respondents' responses; and 3) treatment of the results and interpretation of the data, with the condensation of the information and the correlation of the categories previously found with the theoretical basis regarding the elements found in the interviews. In addition, some excerpts from the interviewees' statements were highlighted with the purpose of illustrating their perception regarding each theme, analyzing the information obtained from the point of view of the principles of Spiritual Intelligence. The results demonstrate that leaders' actions based on the principles of Spiritual Intelligence can help them to inspire and influence relationships in the workplace in a positive way, and can provide employees with a greater sense of belonging, a feeling that the organization's communication it occurs efficiently, opportunities to learn, perception of empathy on the part of colleagues and being in an environment of cooperation and collaboration, among other important elements.
Keywords: Inteligência Espiritual; Liderança; Relações interpessoais; Spiritual Intelligence; Leadership; Interpersonal relationships; ACCNPQ::Ciências Sociais Aplicadas::Administração